Tribal nation : the making of Soviet Turkmenistan - Edgar, Adrienne Lynn, 1960- (ACLS Humanities E-Book., 2006)
In 1917 Turkmenistan was a vague collection of semi-nomadic tribes under Russian domination. This book explores the creation of a Turkmen nation, partly Soviet policy & partly the evolution of indigenous notions of identity. The author offers a scholarly analysis of Soviet nation building in Asia.